2022
DOI: 10.15244/pjoes/146937
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Fundamental Controls on Deformation and Stability of an Active Reservoir Landslide, Southwest China

Abstract: Reservoir landslides are a common type of geological disasters in hydropower surroundings, which cause a severe socio-economic threat to human life [1]. Generally, narrow and steep valleys are prone to landslides [2-4]. Wavefront slopes in reservoir reservoir project area are greatly affected by water level changes and may fail easily [5-7]. For example, the catastrophic Vajont landslide in Italy 1963 and the Qianjianping landslide of China in 2003, both disaster events triggered by the variation of reservoir … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Research has indicated that these conditions can precipitate landslides, especially in the Three Gorges Reservoir region [6]. Reservoir levels and precipitation have a significant impact on landslide stability, with fluctuations in reservoir levels being the primary influencing factor [7]. The reactivation of significant landslides caused by changes in reservoir levels has been documented, such as the Dasha landslide [8].…”
Section: Introductionmentioning
confidence: 99%
“…Research has indicated that these conditions can precipitate landslides, especially in the Three Gorges Reservoir region [6]. Reservoir levels and precipitation have a significant impact on landslide stability, with fluctuations in reservoir levels being the primary influencing factor [7]. The reactivation of significant landslides caused by changes in reservoir levels has been documented, such as the Dasha landslide [8].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the complex force characteristics of submarine tunnels in complex seabed environments under seismic actions, their damage mechanisms are diversified under the effect of earthquakes. Influenced by the interaction between marine engineering geology and tunnel structures, as well as the stability of marine engineering geological bodies, the issue of seismic disasters becomes even more complicated [15][16][17].…”
Section: Introductionmentioning
confidence: 99%